Frequency hopping spread spectrum: history, principles and applications - Ristić, Vladimir B.; Todorović, Branislav M.; Stojanović, Nenad M. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The frequency hopping spread spectrum (FH-SS) technique assumes the carrier generated by the syntesizer to hop from frequency to frequency over a wide bandwidth, according to a pseudonoise code sequence defined by the code sequence generator. The article presents the history,  principles and applications of the FH-SS technique. Both military and commercial applications are discussed.Methods: This article presents an overview of data from the technical literature, with appropriate comments.Results: After presenting the history and principles of the FH-SS technique, the article summarizes its use with examples of military and commercial applications. The importance of using FH-SS in the described applications is highlighted.Conclusion: The FH-SS technique has been successfully implemented in many military and commercial technologies due to its  high protection against interference, making communication difficult for reconnaissance and eavesdropping, and its ability to provide code division multiple access.
Keywords: radio communication; spread spectrum; frequency hopping; bluetooth; global system for mobile communication; unmanned aerial vehicles